Case Report: Immunotherapy for low-grade myofibroblastic sarcoma of the pharynx - Sun, Bao; Luo, Zhiying; Liu, Ping; He, Yan; He, Shasha; Liu, Wenhui (Frontiers in Immunology, 2023)
Low-grade myofibroblastic sarcoma (LGMS) characterized by the increased proliferation of myofibroblasts is a rare type of malignant myofibroblastic tumor that frequently occurs in the head and neck region. Presently, there is no consensus regarding the treatment of LGMS. Here, we report a rare case of LGMS of the pharynx in a 40-year-old male admitted to our hospital. The patient underwent resection for a right metastatic lesion and parapharyngeal mass. However, he had recurrence and multiple metastases without a surgical indication. Then the patient received the treatment of anlotinib plus pembrolizumab for 4 cycles, and there was a partial response (PR) to the treatment. Due to the adverse reaction of anlotinib, the patient subsequently received monotherapy of pembrolizumab for 22 cycles and achieved a complete response (CR). As the first case report of the immunotherapy for LGMS, our study highlights that this strategy may be of great significance to the treatment of LGMS.